2000
DOI: 10.1093/emboj/19.7.1661
|View full text |Cite
|
Sign up to set email alerts
|

A Sm-like protein complex that participates in mRNA degradation

Abstract: In eukaryotes, seven Sm proteins bind to the U1, U2, U4 and U5 spliceosomal snRNAs while seven Smlike proteins (Lsm2p–Lsm8p) are associated with U6 snRNA. Another yeast Sm‐like protein, Lsm1p, does not interact with U6 snRNA. Surprisingly, using the tandem affinity purification (TAP) method, we identified Lsm1p among the subunits associated with Lsm3p. Coprecipitation experiments demonstrated that Lsm1p, together with Lsm2p–Lsm7p, forms a new sevensubunit complex. We purified the two related Sm‐like protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
353
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(384 citation statements)
references
References 83 publications
30
353
0
1
Order By: Relevance
“…These results were almost identical to those obtained in K. lactis and confirmed that the lack of the C-terminal region of the protein severely affects cell viability during the stationary phase. In S. cerevisiae, the role of Lsm4p has been associated with mRNA splicing and decapping (Bouveret et al, 2000;Mayes et al, 1999;Thaurun et al, 2000) and work is in progress to verify whether these processes are altered in the K. lactis and S. cerevisiae strains expressing the truncated form of KlLsm4p. Cells were grown on YPD medium and OD 600 was measured at the indicated times.…”
Section: Complementation Of S Cerevisiaementioning
confidence: 99%
“…These results were almost identical to those obtained in K. lactis and confirmed that the lack of the C-terminal region of the protein severely affects cell viability during the stationary phase. In S. cerevisiae, the role of Lsm4p has been associated with mRNA splicing and decapping (Bouveret et al, 2000;Mayes et al, 1999;Thaurun et al, 2000) and work is in progress to verify whether these processes are altered in the K. lactis and S. cerevisiae strains expressing the truncated form of KlLsm4p. Cells were grown on YPD medium and OD 600 was measured at the indicated times.…”
Section: Complementation Of S Cerevisiaementioning
confidence: 99%
“…These proteins colocalize in discrete cytoplasmic foci in mammalian cells, termed processing bodies or P-bodies (also known as DCP1-or GW182-bodies), indicating that mRNA decay is restricted to distinct cytoplasmic compartments in mammalian cells (van Dijk et al, 2002;Cougot et al, 2004). The human protein CCR4, which is involved in mRNA deadenylation, the decapping stimulating LSm proteins LSm1-7, the DEAD/Hbox RNA helicase DDX6 (also known as RCK/p54), GW182, and Ge-1 are components of P-bodies (Bouveret et al, 2000;Eystathioy et al, 2002;Ingelfinger et al, 2002; LykkeAndersen, 2002;Cougot et al, 2004;Yu et al, 2005). Moreover, the RNA-associated protein 55, hEDC3, Hedls as well as factors of the RISC complex localize to P-bodies in mammalian cells (Fenger-Gron et al, 2005;Liu et al, 2005;Sen and Blau, 2005;Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The most highly characterized Sm/Lsm-containing RNPs are those involved in pre-mRNA splicing, the U1, U2, U4/U6, and U5 small nuclear RNPs (snRNPs) (1), whereas others are known to be important for telomere replication (2), trans-splicing (3), and mRNA degradation (4,5).…”
mentioning
confidence: 99%